MANAGEMENT OF TEACHER PROFESSIONAL DEVELOPMENT (CASE STUDIES SCIENTIFIC PUBLICATIONS OF TEACHER IN SAMBAS, INDONESIA) - Serli, Serli (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
This paper is a case study to identify elements of teacher competence development in the ongoing professional development of teachers in Sambas, Indonesia. Quite difficult to ensure that the implementation process of teacher professional development today, including how the teacher reaction to the declaration of functional regulation of teachers and credit figures that has been in effect since 2013 a go. So the goal of this research is to identify the concept, implementation and management of the response of teachers to the teacher professional development, particularly in the field of scientific publications. This study used a qualitative descriptive approach, as a basic introduction to the field (grand tour of observation), carried out with the documentation and interviews with technique. purposive sampling The findings were obtained: (1) The concept of teacher professional development in the field of scientific publications Sambas district is still not arranged in a programmed and systematic, they are self-supporting, the government has not directly organize scientific papers training; (2) Development of professional competence of teachers is implemented on a limited basis by organizing training scientific papers by involving non goverment organization, the Department of Education and Teachers; (3) The implementation of teacher professional development policies vary by teachers responded, as an opportunity or a threat to the profession as a teacher career advancement. The results of this paper form the basis of teacher professional development program for teachers and decision making, the school, as well as educational and cultural offices.